A qualitative study on the feasibility and acceptability of institutionalizing health technology assessment in Malawi - Joseph Mfutso-Bengo; Faless Jeremiah; Florence Kasende-Chinguwo; Wingston Ng’ambi; Nthanda Nkungula; Isabel Kazanga-Chiumia; Mercy Juma; Marlen Chawani; Jobiba Chinkhumba; Pakwanja Twea; Emily Chirwa; Kate Langwe; et al. (BMC Health Services Research, 2023)
Abstract Objective The objective of this study was to assess the feasibility and acceptability of institutionalizing Health Technology Assessment (HTA) in Malawi. Methods This study employed a document review and qualitative research methods, to understand the status of HTA in Malawi. This was complemented by a review of the status and nature of HTA institutionalization in selected countries.Qualitative research employed a Focus Group Discussion (FGD ) with 7 participants, and Key Informant Interviews (KIIs) with12 informants selected based on their knowledge and expertise in policy processes related to HTA in Malawi.Data extracted from the literature was organized in Microsoft Excel, categorized according to thematic areas and analyzed using a literature review framework. Qualitative data from KIIs and the FGD was analyzed using a thematic content analysis approach. Results Some HTA processes exist and are executed through three structures namely: Ministry of Health Senior Management Team, Technical Working Groups, and Pharmacy and Medicines Regulatory Authority (PMRA) with varyingdegrees of effectiveness.The main limitations of current HTA mechanisms include limited evidence use, lack of a standardized framework for technology adoption, donor pressure, lack of resources for the HTA process and technology acquisition, laws and practices that undermine cost-effectiveness considerations. KII and FGD results showed overwhelming demand for strengthening HTA in Malawi, with a stronger preference for strengthening coordination and capacity of existing entities and structures. Conclusion The study has shown that HTA institutionalization is acceptable and feasible in Malawi. However, the current committee based processes are suboptimal to improve efficiency due to lack of a structured framework. A structured HTA framework has the potential to improve processes in pharmaceuticals and medical technologies decision-making.In the short to medium term, HTA capacity building should focus on generating demand and increasing capacity in cost-effectiveness assessments. Country-specific assessments should precede HTA institutionalization as well as recommendations for new technology adoptions.